Exploring Thai Vernacular Houses for Heritage Tourism along the Western Bangkok Canals - Kiatthanawat, Asadaporn; Yodsurang, Patiphol; Krasae-in, Aracha (Nakhara : Journal of Environmental Design and Planning, 2024)
The tourism industry in Bangkok, Thailand, has predominantly focused on urban attractions within the city, overlooking the significant cultural heritage and historical value of the canal-side areas. This research seeks to explore the untapped potential of heritage canal-side tourism in Western Bangkok. The objective is to identify and map the Thai and vernacular houses situated along the canal in the western region of Bangkok, an area of important cultural and heritage significance, and analyze their clustering and distribution patterns, utilizing a rapid survey—a comprehensive and swift data collection method characterized by quick on-site assessments and visual inspections. The findings reveal three areas around Khlong Bangkok Yai, Khlong Bang Noi and Khlong Bang Chueak Nang, and Khlong Saman Chai connecting to the Khlong Bang Mod that exhibit considerable potential for developing tangible architectural resources, thereby creating scenic attractions for cultural tourism. These results serve as a foundation for further development of the canal-side areas as tourist destinations, showcasing their unique historic scenery of architectural charm and cultural heritage.